2012
DOI: 10.1299/jtst.7.90
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Diesel Cetane Number on Exhaust Emissions Characteristics by Various Additives

Abstract: This paper described the effect of the diesel cetane number on exhaust emissions characteristics according to various additives. In addition, the emission characteristics of test fuels blended with three additives (GTL, biodiesel and additive for improving CN) were analyzed and the potential for uses of these additives were evaluated in this study. To achieve this purpose, the test diesel vehicle with a two-thousand cubic centimeter displacement was used to analyze the emission characteristics according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Additionally, it was observed that all aromatics have a higher PM formation tendency than paraffins . This may explain the PM reduction in the case of HVO blend, however, the opposite tendency was also obtained and was attributed to the improved cetane number in comparison to diesel fuel, resulting in a reduction of the premixed combustion region, while diffusion combustion increases . As shown by Happonen and co-workers even higher PM emissions reductions are possible by blending HVO fuel with a suitable oxygenate.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Additionally, it was observed that all aromatics have a higher PM formation tendency than paraffins . This may explain the PM reduction in the case of HVO blend, however, the opposite tendency was also obtained and was attributed to the improved cetane number in comparison to diesel fuel, resulting in a reduction of the premixed combustion region, while diffusion combustion increases . As shown by Happonen and co-workers even higher PM emissions reductions are possible by blending HVO fuel with a suitable oxygenate.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, pure HVO has a very high cetane number (>70) and its addition to diesel fuel increases the cetane number linearly. It was found that increased cetane number also reduced emissions of HC and CO, probably due to improvement of ignition performance …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this connection, extensive study is going on to improve the performance of diesel engine by doping diesel fuel with specific nanomaterials. Doping will not only enhance the thermal efficiency of engine bust also accounts for reduction of emissions from the combustion 8,9 . In recent years, many researchers have worked in this theme and reported the influence of various fuel additives such as metal oxide in nanoscale form.…”
Section: Introductionmentioning
confidence: 99%